1991
DOI: 10.1207/s15327906mbr2602_4
|View full text |Cite
|
Sign up to set email alerts
|

A Bootstrap Confidence Interval Based on a Correlation Corrected for Range Restriction

Abstract: The sample correlation coefficient corrected for range restriction was bootstrapped to obtain a confidence interval on the unrestricted population correlation, rho. The technique was evaluated using a computer simulation under different values of rho and four distributions (normal, mixed, positively skewed and negatively skewed). The corrected correlation coefficient yielded accurate bootstrap intervals over the four distributions. On the average, the size of rho did not affect the accuracy of the confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
3
26
0
Order By: Relevance
“…Duan and Dunlap (1997) provided a summary of these methods and evaluate their empirical performance. Rather than the asymptotic approach, Mendoza, Hart, and Powell (1991) proposed a resampling technique to obtain the bootstrap SE, and argued that a better CI could be constructed. Chan and Chan (2004) further evaluated Mendoza et al's bootstrap procedure by a more comprehensive simulation study, and found generally comparable results to those of Mendoza et al…”
Section: Discussionmentioning
confidence: 99%
“…Duan and Dunlap (1997) provided a summary of these methods and evaluate their empirical performance. Rather than the asymptotic approach, Mendoza, Hart, and Powell (1991) proposed a resampling technique to obtain the bootstrap SE, and argued that a better CI could be constructed. Chan and Chan (2004) further evaluated Mendoza et al's bootstrap procedure by a more comprehensive simulation study, and found generally comparable results to those of Mendoza et al…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the statistics and economics literature considers the classical "restrictionof-range" problem (DeMets and Halperin, 1977;Duan and Dunlap, 1997;Johnson and Ree, 1994;Held and Foley, 1994;Mendoza et al 1991;Hanges et al 1991;Holmes, 1990). In this literature, correlations, or more generally regression coefficients are shown to be affected by focusing the analysis on a small slice of the population.…”
Section: Relationship To Other Literaturementioning
confidence: 99%
“…Since Pearson (1903) developed the correction formulas for restriction in range and Thorndike ( 1947,1949) defined them for practical application, educational and personnel psychologists have conducted extensive research on the problem of restriction in range (Alexander, Carson, Alliger, & Barrett, 1984;Booth-Kewley, 1985;Greener & Osburn, 1979;Gross & Fleischman, 1983;Levin, 1972;Linn, 1968;Linn, Harnisch, & Dunbar, 1981;Mendoza, Hart, & Powell, 1991;Olson & Becker, 1983;Sands, Alf, & Abrahams, 1978). However, most of the research pertains to the univariate, not the multivariate, correction formulas (Lord & Novick, 1968;Novick & Thayer, 1969).…”
mentioning
confidence: 99%